Analisis Perolehan Suara Partai Golkar Pada Pemilu 1999 di Indonesia - Yunda Pratiwi (Dinamika Politik, 2012)
This study is a study of the decline of Acquisition of Golkar Party Vote in Election 1999 in Indonesia. The focus discusses what caused the decline in the number of votes of the Golkar Party in the 1999 general election in Indonesia. The findings of this study, among others, there are four important things behind the decline in the number of votes of the Golkar Party in the 1999 election. First, the monetary crisis, and second, changes in national politics; Third, removal monoloyalitas civil / military; fourth, political pressure and the rift within Golkar. The method used is descriptive-qualitative method that is intended to describe an event in more detail.Keywords: Golkar, Elections, Post-Reformation.